Estudo teórico do espalhamento de elétrons por radicais livres - Souza, Gabriel Luiz Cruz de (2007)
In this present work, we have carried out some calculations of electron-radicals scattering cross sections in the lowjintermediate energy range. Differential, integral, momentum transfer, total and total of absorption cross sections were calculated for the electron-SiF j SiF2 scattering in the energy range between 1,0-1000 eV. The dynamics of electron-molecule interaction is described by a complex optical potential formed by static, exchange, correlation-polarization and absorption contributions. The Schwinger variational iterative method combined with distorted-wave approximation is applied to calculate the scattering amplitudes. Some of the results presented here are compareci with the experimental andj or theoretical results available in the literature.